Elementary engineering drawing: plane and solid geometry - Bhatt, N. D (Charotar Publishing House, 2005)
Elementary engineering drawing: plane and solid geometry / Bhatt, N. D. -- Anand: Charotar Publishing House, 2005 604.2 B575e48 48th ed. No. of Copies : 1